Smart applications of bionanosensors for BCR/ABL fusion gene detection in leukemia - Karen Y.P.S. Avelino; Rafael R. Silva; Alberto G. da Silva Junior; Maria D.L. Oliveira; César A.S. Andrade (Journal of King Saud University: Science, 2017)
The present review discuss the relevance and innovative state-of-the-art on molecular diagnosis of leukemia. This morbidity is one of the most common types of cancer with an annual incidence of 250,000 new cases. The prevalence of leukemia among children up to 15 years of age is 30% on all cases of cancer reported in the childhood. The BCR/ABL fusion gene is one of the most important biomarkers in leukemia, being found in all cases of chronic myeloid leukemia and up to 40% of cases of acute lymphoblastic leukemia. Genosensors are considered smart devices for identification of BCR/ABL fusion gene in clinical samples. Molecular techniques can contribute to early diagnosis of cancer, monitoring of minimal residual disease and implementation of effective drug therapies. The present review presents the scientific advances in the last decades on DNA biosensors constructed for BCR/ABL fusion gene detection. The assembly of nanostructured platforms, molecular immobilization strategies and analytical performances of the biodevices are discussed. The present review assesses the potential of electrochemical and optical techniques for BCR/ABL fusion gene detection. Electrochemical genosensors based on engineered nanomaterials at the transduction interface are useful to obtain high levels of sensitivity (up to 10−18 M). On the other hand, optical genosensors had higher detection limits (10−15 M). The analytical response time and reusability of genosensors for BCR/ABL fusion gene identification in small sample volumes (in the order of μL) were discussed. The present review highlighted nanostructured platforms as promising tool for diagnosis and monitoring of BCR/ABL fusion gene in leukemia patients.